CORPORATE FORESIGHT AND ORGANISATIONAL SUSTAINABILITY OF OIL SERVICING COMPANIES IN THE NIGER DELTA REGION, SOUTH-SOUTH, NIGERIA - Onyema, Lawrence; Aaron, Agbeche; Pope, Odili; Subai, Amadi (Journal of Strategic Management, 2020)
Purpose: The main purpose for this research was to determine the degree at which oil servicing companies' corporate foresight in the Niger Delta Region of Nigeria influences the firm's sustainability in that region and how the firms are able to take advantage of future competitive advantages. Methodology: This research adopts the descriptive survey design with the application of simple random sampling technique. Questionnaires were the primary means for gathering data from the employees in the oil servicing industry. A total of one hundred and fifty four questionnaires were administered to the senior staff in the selected oil servicing companies in Niger Delta region. The data collected was analyzed using descriptive and correlational analysis and supported with statistical package for social science (SPSS). Findings: organizational sustainability in oil servicing companies in the Niger Delta region of Nigeria with emphases to the measures of sustainability like social, environmental and economic. Unique contribution: The study gave useful perception of oil companies by stating that oil companies' personnel or managers who are future oriented are the wheel upon which the companies' future depends.